Being humorous at work: the role of gelotophobia on affect and organizational climate - Junça Silva, A.; Caetano, António; Lopes, M. (31st International Congress in Psychology, 2016)
Increasing attention has been given to employees´ happiness in the form of pleasant moods and emotions, well-being and positive attitudes. This symposium proposal aims to conceptualize and measure well-being at work through four different studies. The first study intends to analyze if coping moderates the relationship between organizational practices and subjective well-being. The second study is framed on the Work-Home Resource Model and is focused on contextual resources of the family and personal resources in relation to flourishing at work. Moreover, the study explores the mediating role of core self-evaluations on such relationships. The third study, encompasses a quasi-experimental design in order to explore the relationship between humor events at work, affect and organizational climate. Plus, this study also analyzes the moderating role of gelotophobia in the link humor events – affect. Finally, the fourth study is framed on the activation theory. This study intends to explore the moderating role of mindfulness on the relationship between two role stressors and innovative work behavior. This symposium will consider theoretical and practical problems facing the research of well-being at work and present perspectives for future research.